Improved structure and highly conductive lignin-carbon fibers through graphene oxide liquid crystal. (15th August 2020) - Torres-Canas, Fernando; Bentaleb, Ahmed; Fӧllmer, Marie; Roman, Julien; Neri, Wilfrid; Ly, Isabelle; Derré, Alain; Poulin, Philippe
Abstract: Lignin is considered as a promising bio-sourced precursor for more sustainable and low-cost carbon fibers (CFs). However, lignin-based CFs generally have a poor graphitic structure, compared to polyacrylonitrile CFs. In this paper, we present an original approach that uses graphene oxide liquid crystal (GOLC) as a templating agent to promote the formation of graphitic structure in the fibers at low carbonization temperature. Both lignin and hybrid lignin/GOLC CFs were carbonized/graphitized up to 2700 °C. Structural analyses by X-ray diffraction, Raman spectroscopy and electrical measurements manifest a significant improvement in graphitic structure and a preferred orientation of graphene planes for lignin/GOLC fibers. These effects are the result of axial propagation of the templated graphitic order nucleated by the large GO flakes. The current approach reveals the possibility of preparing low-cost lignin-based CFs with improved graphitic structure and high electrical conductivity at low temperature for electrochemical or smart textile applications. Graphical abstract: Image 1